Crosslinkable composition and molded article
By using a crosslinking composition of fluoroelastomer and a solid solution of alumina and magnesium oxide, the problem of insufficient heat resistance and expansion resistance of molded products in the prior art at high temperatures is solved, and a molded product with better urea water resistance, ammonia water resistance and heat resistance is achieved.
Patent Information
- Application Number
- CN202380054244.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-07-25
- Filing Date
- 2023-07-24
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to simultaneously improve molded products with excellent urea water properties, ammonia water properties and heat resistance. Especially under high temperature conditions, there is still room for improvement in the heat resistance and expansion resistance of the molded products.
A crosslinkable composition containing a solid solution of fluoroelastomer and a solid solution of alumina and magnesium oxide is used to make a molded product by crosslinking to improve its urea water resistance, ammonia water resistance and heat resistance.
The heat resistance and expansion resistance of the molded product under high temperature conditions have been significantly improved, while maintaining excellent urea water resistance and ammonia water resistance. The tensile strength change rate is only above -25% after heating at 240°C for 72 hours.
Smart Images

Figure CN119731261A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a crosslinkable composition and a molded article. Background Art
[0002] Patent Document 1 describes a component comprising a fluorinated elastomer composition, which is a component facing ammonia and / or urea and has a surface in contact with at least one of urea and ammonia, wherein the surface comprises a fluorinated polymer and a hydrotalcite compound.
[0003] Patent Document 2 describes a urea SCR system component, characterized in that it is obtained by crosslinking a crosslinkable composition comprising a fluorine-containing polymer having a glass transition temperature of 25° C. or less and a crosslinking agent, wherein the fluorine-containing polymer is composed of vinylidene fluoride and the following general formula (1):
[0004] CH2=CFRf (1)
[0005] (In the formula, Rf is a linear or branched fluorinated alkyl group having 1 to 12 carbon atoms.)
[0006] A copolymer composed of the fluorinated monomer (1) shown.
[0007] Patent Document 3 describes a fluororubber composition characterized by containing a fluororubber and at least one selected from the group consisting of aluminum silicate and synthetic magnesium silicate.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application No. 2017-500397
[0011] Patent Document 2: Japanese Patent Application Publication No. 2016-131953
[0012] Patent Document 3: Japanese Patent Application Publication No. 2019-094370 Summary of the invention
[0013] Problems to be solved by the invention
[0014] An object of the present invention is to provide a cross-linkable composition capable of obtaining a molded article having excellent resistance to urea solution and ammonia solution and also excellent heat resistance.
[0015] Means for solving problems
[0016] According to the present invention, there is provided a crosslinkable composition comprising a fluororubber and a solid solution of aluminum oxide and magnesium oxide.
[0017] Effects of the Invention
[0018] According to the present invention, there can be provided a cross-linkable composition capable of obtaining a molded article having excellent resistance to urea water and ammonia water and also excellent heat resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 It is a schematic diagram showing an example of a urea SCR system. DETAILED DESCRIPTION
[0020] Hereinafter, specific embodiments of the present invention will be described in detail, but the present invention is not limited to the following embodiments.
[0021] Patent Document 1 proposes a fluorinated elastomer composition comprising a fluorinated polymer and a hydrotalcite compound as a fluorinated elastomer composition having resistance when in contact with urea and / or ammonia.
[0022] However, there is a demand for further improvement in the urea water resistance and ammonia water resistance of molded products.
[0023] In addition, it is known that even if a hydrotalcite compound is mixed with fluororubber, the heat resistance of the molded product is hardly improved. Patent Document 1 states that urea may decompose at particularly high temperatures (e.g., >100°C) to generate ammonia, and that a fluoroelastomer composition comprising a partially fluorinated elastomer polymer and hydrotalcite can achieve improved expansion resistance to ammonia under high temperature conditions, but a technology is required to improve not only the expansion resistance to ammonia but also the heat resistance of the molded product itself.
[0024] The crosslinkable composition of the present invention contains fluororubber and a solid solution of aluminum oxide and magnesium oxide. The crosslinkable composition of the present invention contains a solid solution of aluminum oxide and magnesium oxide mixed in the fluororubber, so by crosslinking the crosslinkable composition of the present invention to form a molded article, a molded article having excellent resistance to urea water and ammonia water and excellent heat resistance can be obtained.
[0025] In the present invention, "urea water resistance" refers to the property that the volume and mass of the molded product are not easily changed even when in contact with urea water. Urea includes urea and polyurea. Urea can also be urea water.
[0026] In the present invention, "ammonia water resistance" refers to the property that the volume and mass of the molded product are not easily changed even when in contact with ammonia water. Ammonia includes ammonia, ammonium hydroxide and ammonium alkoxide. Ammonia can be in gaseous form or liquid form. Ammonia can also be ammonia water.
[0027] In the present invention, "heat resistance" means that the tensile strength of the molded article is not easily reduced even when heated at high temperatures. For example, even when the molded article obtained from the crosslinkable composition of the present invention is heated at 240°C for 72 hours, the change rate of tensile strength calculated by the calculation formula described below is -25% or more.
[0028] (Fluororubber)
[0029] The cross-linkable composition of the present invention contains fluororubber. In the present invention, fluororubber refers to an amorphous fluoropolymer. "Amorphous" means that the size of the melting peak (ΔH) appearing in the differential scanning calorimetry [DSC] (heating temperature 20°C / min) or differential thermal analysis [DTA] (heating rate 20°C / min) of the fluoropolymer is 4.5 J / g or less. Fluororubber exhibits elastomeric properties by cross-linking. Elastomeric properties refer to the following properties: the polymer can be stretched and its original length can be maintained when the force required to stretch the polymer is no longer applied.
[0030] The fluororubber may be a partially fluorinated rubber or a perfluororubber.
[0031] In the present invention, the partially fluorinated rubber refers to a fluorinated polymer containing fluorinated monomer units and perfluorinated monomer units in an amount of less than 90 mol % relative to all polymerized units, and has a glass transition temperature of 20° C. or less and a melting peak (ΔH) of 4.5 J / g or less.
[0032] In the present invention, perfluoro rubber (perfluoroelastomer) refers to a fluorine-containing polymer in which the content of perfluoro monomer units relative to all polymerized units is 90 mol% or more, preferably 91 mol% or more, and has a glass transition temperature of 20°C or less and a melting peak (ΔH) of 4.5 J / g or less, and further, a polymer in which the concentration of fluorine atoms contained in the fluorine-containing polymer is 71 mass % or more, preferably 71.5 mass % or more. In the present invention, the concentration of fluorine atoms contained in the fluorine-containing polymer is calculated by the type and content of each monomer constituting the fluorine-containing polymer to obtain the concentration (mass %) of fluorine atoms contained in the fluorine-containing polymer.
[0033] In the present invention, a perfluoromonomer refers to a monomer that does not contain a carbon atom-hydrogen atom bond in the molecule. The above-mentioned perfluoromonomer may also be a monomer in which several fluorine atoms bonded to carbon atoms are replaced by chlorine atoms in addition to carbon atoms and fluorine atoms, or a monomer that has nitrogen atoms, oxygen atoms, sulfur atoms, phosphorus atoms, boron atoms or silicon atoms in addition to carbon atoms. As the above-mentioned perfluoromonomer, a monomer in which all hydrogen atoms are replaced by fluorine atoms is preferred. The above-mentioned perfluoromonomer does not contain a monomer that provides a crosslinking site.
[0034] The monomer providing a crosslinking site is a monomer having a crosslinking group (curing site monomer) which provides a crosslinking site for forming a crosslink with a crosslinking agent to the fluorine-containing polymer.
[0035] The fluororubber used in the present invention is not particularly limited, and examples thereof include fluororubber capable of peroxide crosslinking, fluororubber capable of polyol crosslinking, etc. In addition, it may be a crosslinkable fluororubber using a pyridinium salt as described in JP-T 2018-514627.
[0036] The fluororubber capable of polyol crosslinking is a fluororubber having a portion capable of polyol crosslinking. As the fluororubber capable of polyol crosslinking, a partially fluorinated rubber capable of polyol crosslinking is preferred. As the fluororubber capable of polyol crosslinking, there is no particular limitation, and examples thereof include vinylidene fluoride (VdF) based fluororubbers.
[0037] As fluororubber, from the aspect of being able to obtain molded products with better urea water resistance, ammonia water resistance and heat resistance, fluororubber that can be cross-linked by peroxide is preferred. There is no particular limitation on the fluororubber that can be cross-linked by peroxide, as long as it is a fluororubber that has a site that can be cross-linked by peroxide. There is no particular limitation on the site that can be cross-linked by peroxide, and examples thereof include iodine atoms, bromine atoms, and CN groups possessed by fluororubber; unsaturated bonds between carbons in the main chain or side chain of fluororubber; and the like.
[0038] When the fluororubber contains iodine atoms, the iodine content is preferably 0.001 mass % to 10 mass %, more preferably 0.01 mass % or more, preferably 0.1 mass % or more, and more preferably 5 mass % or less.
[0039] The fluororubber may be a partially fluorinated rubber or a perfluororubber. As the fluororubber, from the viewpoint of being able to obtain a molded product with better urea water resistance, ammonia water resistance and heat resistance, and also being advantageous in terms of cost, a partially fluorinated rubber is preferred, and a partially fluorinated rubber capable of being cross-linked by peroxide is more preferred. Below, the monomer composition of the fluororubber is described in detail, but the monomer composition described in detail below is suitable as a monomer composition of a fluororubber capable of being cross-linked by peroxide and a fluororubber capable of being cross-linked by polyol, and is particularly suitable as a monomer composition of a fluororubber capable of being cross-linked by peroxide.
[0040] As the partially fluorinated rubber, it is preferred to contain, for example, a compound selected from tetrafluoroethylene (TFE), vinylidene fluoride (VdF) and a compound of the general formula: CF2=CF-Rf a (Where Rf a -CF3 or -ORf b (Rf bThe partially fluorinated rubber preferably contains a VdF unit or a TFE unit.
[0041] As the partially fluorinated rubber, there can be mentioned vinylidene fluoride (VdF) based fluororubber, tetrafluoroethylene (TFE) / propylene (Pr) based fluororubber, tetrafluoroethylene (TFE) / propylene / vinylidene fluoride (VdF) based fluororubber, ethylene / hexafluoropropylene (HFP) based fluororubber, ethylene / hexafluoropropylene (HFP) / vinylidene fluoride (VdF) based fluororubber, ethylene / hexafluoropropylene (HFP) / tetrafluoroethylene (TFE) based fluororubber, etc. Among them, at least one selected from the group consisting of vinylidene fluoride based fluororubber and tetrafluoroethylene / propylene based fluororubber is preferred.
[0042] As the fluororubber, from the perspective of being able to obtain a molded product with better resistance to urea water, ammonia water and heat resistance, it is preferred to select at least one from the group consisting of vinylidene fluoride fluororubber, tetrafluoroethylene / propylene fluororubber and perfluororubber, and more preferably at least one from the group consisting of vinylidene fluoride fluororubber and tetrafluoroethylene / propylene fluororubber.
[0043] As the vinylidene fluoride-based fluororubber, a copolymer composed of 45 mol % to 85 mol % of vinylidene fluoride and 55 mol % to 15 mol % of at least one other monomer copolymerizable with vinylidene fluoride is preferred, and a copolymer composed of 50 mol % to 80 mol % of vinylidene fluoride and 50 mol % to 20 mol % of at least one other monomer copolymerizable with vinylidene fluoride is more preferred.
[0044] Examples of at least one other monomer copolymerizable with vinylidene fluoride include tetrafluoroethylene [TFE], hexafluoropropylene [HFP], fluoroalkyl vinyl ether, chlorotrifluoroethylene [CTFE], trifluoroethylene, trifluoropropylene, pentafluoropropylene, trifluorobutylene, tetrafluoroisobutylene, hexafluoroisobutylene, vinyl fluoride, and the general formula (100): CHX 101 =CX 102 R 101 (Where X 101 and X 102 One of them is H and the other is F, Rf 101 is a fluorinated monomer represented by a linear or branched fluoroalkyl group having 1 to 12 carbon atoms, general formula (170): CH2=CH-(CF2) n -X 171 (Where X 171is H or F, n is an integer of 3 to 10), monomers such as monomers providing crosslinking sites, and non-fluorinated monomers such as ethylene, propylene, and alkyl vinyl ether. They can be used alone or in any combination.
[0045] As the fluoroalkyl vinyl ether, perfluoro(methyl vinyl ether) or perfluoro(propyl vinyl ether) is preferred, and perfluoro(methyl vinyl ether) is more preferred. These may be used alone or in any combination.
[0046] The fluorine-containing monomer represented by the general formula (100) is preferably 2,3,3,3-tetrafluoropropylene or 1,3,3,3-tetrafluoropropylene, and more preferably 2,3,3,3-tetrafluoropropylene.
[0047] The at least one other monomer copolymerizable with vinylidene fluoride is preferably at least one selected from the group consisting of TFE, HFP, fluoroalkyl vinyl ether, CTFE and a fluorinated monomer represented by the general formula (100), and more preferably at least one selected from the group consisting of TFE, HFP, fluoroalkyl vinyl ether and 2,3,3,3-tetrafluoropropylene.
[0048] Specific examples of vinylidene fluoride-based fluororubbers include VdF / HFP-based rubbers, VdF / HFP / TFE-based rubbers, VdF / CTFE-based rubbers, VdF / CTFE / TFE-based rubbers, VdF / fluorinated monomer-based rubbers represented by the general formula (100), VdF / fluorinated monomer-based rubbers represented by the general formula (100) / TFE-based rubbers, VdF / perfluoro(methyl vinyl ether) [PMVE]-based rubbers, VdF / PMVE / TFE-based rubbers, and VdF / PMVE / TFE / HFP-based rubbers. Among these, at least one copolymer selected from the group consisting of VdF / HFP-based rubbers, VdF / HFP / TFE-based rubbers, and VdF / 2,3,3,3-tetrafluoropropylene-based rubbers is preferred.
[0049] As the VdF / HFP-based rubber, the molar ratio of VdF / HFP is preferably 45 to 85 / 55 to 15, more preferably 50 to 80 / 50 to 20, and even more preferably 60 to 80 / 40 to 20.
[0050] As the VdF / HFP / TFE-based rubber, the molar ratio of VdF / HFP / TFE is preferably 40 to 80 / 10 to 35 / 10 to 35.
[0051] As the VdF / 2,3,3,3-tetrafluoropropylene rubber, the molar ratio of VdF / 2,3,3,3-tetrafluoropropylene is preferably 45 to 85 / 55 to 15, more preferably 50 to 80 / 50 to 20, and even more preferably 60 to 80 / 40 to 20.
[0052] The tetrafluoroethylene / propylene fluororubber is preferably a copolymer composed of 45 mol% to 70 mol% of tetrafluoroethylene, 55 mol% to 30 mol% of propylene, and 0 to 5 mol% of a fluorine-containing monomer providing a crosslinking site.
[0053] The perfluororubber is preferably a perfluororubber containing TFE, for example, at least one selected from the group consisting of a copolymer of TFE / a fluorinated monomer represented by the general formula (11), (12) or (13) and a copolymer of TFE / a fluorinated monomer represented by the general formula (11), (12) or (13) / a monomer providing a crosslinking site.
[0054] Preferred general formula (11): CF2=CF-ORf 111
[0055] (Where Rf 111 represents a fluorinated monomer represented by a perfluoroalkyl group having 1 to 10 carbon atoms. 111 A perfluoroalkyl group having 1 to 5 carbon atoms is preferred.
[0056] General formula (12): CF2=CFOCF2ORf 121
[0057] (Where Rf 121 A fluorinated monomer represented by a linear or branched perfluoroalkyl group having 1 to 6 carbon atoms, a cyclic perfluoroalkyl group having 5 to 6 carbon atoms, or a linear or branched perfluorooxyalkyl group having 2 to 6 carbon atoms and containing 1 to 3 oxygen atoms
[0058] General formula (13): CF2=CFO(CF2CF(Y 131 )O) m (CF2) n F
[0059] (Where Y 131 represents a fluorine atom or a trifluoromethyl group. m is an integer from 1 to 4. n is an integer from 1 to 4. ) represents a fluorine-containing monomer
[0060] The fluorinated monomer represented by the general formula (11) is preferably at least one selected from the group consisting of perfluoro(methyl vinyl ether), perfluoro(ethyl vinyl ether) and perfluoro(propyl vinyl ether), and more preferably at least one selected from the group consisting of perfluoro(methyl vinyl ether) and perfluoro(propyl vinyl ether).
[0061] The fluorine-containing monomer represented by the general formula (12) is preferably at least one selected from the group consisting of CF2=CFOCF2OCF3, CF2=CFOCF2OCF2CF3 and CF2=CFOCF2OCF2CF2OCF3.
[0062] The fluorinated monomer represented by the general formula (13) is preferably at least one selected from the group consisting of CF2=CFOCF2CF(CF3)O(CF2)3F, CF2=CFO(CF2CF(CF3)O)2(CF2)3F and CF2=CFO(CF2CF(CF3)O)2(CF2)2F.
[0063] The composition of the TFE / PMVE copolymer is preferably 45 to 90 / 10 to 55 (mol %), more preferably 55 to 80 / 20 to 45, and further preferably 55 to 70 / 30 to 45.
[0064] The copolymer composition of TFE / PMVE / crosslinking site providing monomer is preferably 45 to 89.9 / 10 to 54.9 / 0.01 to 4 (mol %), more preferably 55 to 77.9 / 20 to 49.9 / 0.1 to 3.5, and further preferably 55 to 69.8 / 30 to 44.8 / 0.2 to 3.
[0065] The composition of the copolymer of TFE / fluorinated monomer represented by the general formula (11), (12) or (13) having 4 to 12 carbon atoms is preferably 50 to 90 / 10 to 50 (mol %), more preferably 60 to 88 / 12 to 40, further preferably 65 to 85 / 15 to 35.
[0066] The copolymer composition of TFE / fluorinated monomer represented by the general formula (11), (12) or (13) having 4 to 12 carbon atoms / monomer providing a crosslinking site is preferably 50 to 89.9 / 10 to 49.9 / 0.01 to 4 (mol %), more preferably 60 to 87.9 / 12 to 39.9 / 0.1 to 3.5, and still more preferably 65 to 84.8 / 15 to 34.8 / 0.2 to 3.
[0067] Outside these composition ranges, the properties as a rubber elastic body are lost and properties close to those of a resin tend to be exhibited.
[0068] The perfluororubber is preferably at least one selected from the group consisting of a copolymer of TFE / fluorinated monomer represented by the general formula (13) / fluorinated monomer providing a crosslinking site, a copolymer of TFE / perfluorovinyl ether represented by the general formula (13), a copolymer of TFE / fluorinated monomer represented by the general formula (11), and a copolymer of TFE / fluorinated monomer represented by the general formula (11) / monomer providing a crosslinking site.
[0069] Examples of the perfluororubber include perfluororubbers described in International Publication No. 97 / 24381, Japanese Examined Patent Publication No. 61-57324, Japanese Examined Patent Publication No. 4-8118, Japanese Examined Patent Publication No. 5-13961, and the like.
[0070] Fluororubber is also preferably composed of a copolymer containing polymerization units from monomers providing crosslinking sites. As monomers providing crosslinking sites, for example, iodine-containing monomers such as perfluoro(6,6-dihydro-6-iodo-3-oxa-1-hexene) and perfluoro(5-iodo-3-oxa-1-pentene) described in Japanese Patent Publication No. 5-63482 and Japanese Patent Publication No. 7-316234, bromine-containing monomers described in Japanese Patent Publication No. 4-505341, cyano-containing monomers, carboxyl-containing monomers, and alkoxycarbonyl-containing monomers described in Japanese Patent Publication No. 4-505345 and Japanese Patent Publication No. 5-500070 can be cited.
[0071] Fluororubber can be obtained by using a chain transfer agent during polymerization. As the chain transfer agent, a bromine compound or an iodine compound can be used. As a polymerization method using a bromine compound or an iodine compound, for example, the following method can be cited: in a substantially oxygen-free state, in the presence of a bromine compound or an iodine compound, emulsion polymerization is carried out in an aqueous medium while applying pressure (iodine transfer polymerization method). As a representative example of the bromine compound or iodine compound used, for example, the general formula can be cited:
[0072] R 2 I x Br y
[0073] (where x and y are integers from 0 to 2 and satisfy 1≤x+y≤2, R 2 A compound represented by a saturated or unsaturated fluorinated hydrocarbon group or chlorofluorocarbon group having 1 to 16 carbon atoms, or a hydrocarbon group having 1 to 3 carbon atoms, which may contain an oxygen atom). By using a bromine compound or an iodine compound, iodine or bromine is introduced into the polymer to function as a crosslinking point.
[0074] The fluorine content of the fluororubber is preferably 55% to 73% by mass, more preferably 61% by mass or more, further preferably 63% by mass or more, further preferably 65% by mass or more, particularly preferably 67% by mass or more, most preferably 69% by mass or more, and more preferably less than 71% by mass. The fluorine content of the fluororubber can be determined by 19 The composition of the fluororubber measured by F-NMR was determined by calculation.
[0075] The Mooney viscosity (ML1+10(121°C)) of the fluororubber at 121°C is preferably 2 or more, more preferably 5 or more, and even more preferably 10 or more. In addition, it is preferably 200 or less, more preferably 120 or less, even more preferably 100 or less, and particularly preferably 80 or less. The Mooney viscosity is a value measured in accordance with ASTM-D1646-15 and JIS K6300-1:2013.
[0076] (Solid solution)
[0077] The crosslinkable composition of the present invention contains a solid solution of alumina and magnesia.
[0078] The solid solution of alumina and magnesia may have, for example, the following formula:
[0079] (Mg 1-x Al x )O 1+0.5x
[0080] (where 0 < x < 0.4.) The chemical composition shown.
[0081] The solid solution of alumina and magnesia may have, for example, Mg 0.7 Al 0.3 O 1.15 The chemical composition shown.
[0082] The solid solution is generally distinguished from the hydrotalcite compound containing anions in terms of not containing anions.
[0083] The content of alumina (Al2O3) in the solid solution is, for example, 10% by mass to 40% by mass relative to the mass of the solid solution. In addition, the content of magnesia (MgO) in the solid solution is, for example, 90% by mass to 60% by mass relative to the mass of the solid solution.
[0084] In the crosslinkable composition of the present invention, from the aspect of being able to obtain a molded product with more excellent urea resistance, ammonia resistance and heat resistance, the content of the solid solution is preferably 0.5 parts by mass to 10 parts by mass, more preferably 1.0 part by mass or more, more preferably 8 parts by mass or less, further preferably 6 parts by mass or less, and particularly preferably 4 parts by mass or less relative to 100 parts by mass of the fluororubber.
[0085] (Crosslinking agent)
[0086] The crosslinkable composition of the present invention preferably further contains a crosslinking agent. As the crosslinking agent, crosslinking agents commonly used in polyol crosslinking, polyamine crosslinking and peroxide crosslinking can be cited. As the crosslinking agent, at least 1 selected from the group consisting of polyhydroxy compounds, polyamine compounds and peroxides is preferred, and an organic peroxide is more preferred. When emphasizing the acid resistance of the member, peroxide crosslinking is preferred, but in the case of forming a laminate or composite part by vulcanizing and bonding a fluororubber crosslinked product with other materials and when it is difficult to sufficiently vulcanize and bond in peroxide crosslinking, it is sometimes necessary to select polyol crosslinking to balance acid resistance and adhesiveness.
[0087] In the case where the crosslinkable composition of the present invention contains a fluororubber capable of polyol crosslinking, it is preferred to contain a polyhydroxy compound as a crosslinking agent. In the case where the crosslinkable composition of the present invention contains a fluororubber capable of peroxide crosslinking, it is preferred to contain an organic peroxide as a crosslinking agent. In addition, as a fluororubber, when a crosslinkable fluororubber using a pyridinium salt described in Japanese Patent Publication No. 2018-514627 is used, a pyridinium salt can be used as a crosslinking agent. Furthermore, as a fluororubber, when a crosslinkable fluororubber using a curing agent containing a terminal olefin having at least one olefinic hydrogen as described in Japanese Patent Publication No. 2017-538023 is used, a terminal olefin having at least one olefinic hydrogen can be used as a crosslinking agent. As a fluororubber, when a crosslinkable fluororubber using a phthalonitrile compound described in International Publication No. 2020 / 245683 is used, a phthalonitrile compound can be used as a crosslinking agent.
[0088] Furthermore, the crosslinkable composition of the present invention may contain a crosslinking accelerator, a basic compound, a polyfunctional crosslinking auxiliary agent, and the like.
[0089] As the polyhydroxy compound, a polyhydroxy aromatic compound is preferably used from the aspect of excellent heat resistance. The polyhydroxy aromatic compound is not particularly limited, and examples thereof include 2,2-bis(4-hydroxyphenyl)propane (hereinafter referred to as bisphenol A), 2,2-bis(4-hydroxyphenyl)perfluoropropane (hereinafter referred to as bisphenol AF), resorcinol, 1,3-dihydroxybenzene, 1,7-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 2,6-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl, and 4,4'-dihydroxyphenylene. alcohol, 2,6-dihydroxyanthracene, hydroquinone, catechol, 2,2-bis(4-hydroxyphenyl)butane (hereinafter referred to as bisphenol B), 4,4-bis(4-hydroxyphenyl)valeric acid, 2,2-bis(4-hydroxyphenyl)tetrafluorodichloropropane, 4,4'-dihydroxydiphenyl sulfone, 4,4'-dihydroxydiphenyl ketone, tris(4-hydroxyphenyl)methane, 3,3',5,5'-tetrachlorobisphenol A, 3,3',5,5'-tetrabromobisphenol A, etc.
[0090] The content of the polyhydroxy compound is preferably 0.05 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the fluororubber.
[0091] Crosslinking agents such as polyhydroxy compounds can be mixed with other compounds for use. As a mixture containing a crosslinking agent, for example, a solid solution of a crosslinking agent and a crosslinking accelerator, a mixture of a crosslinking agent and a compound capable of dissolving the crosslinking agent, etc. can be cited. As a solid solution, a solid solution of a crosslinking agent and a quaternary phosphonium salt is preferred. As a quaternary phosphonium salt, benzyltriphenylphosphonium chloride is preferred.
[0092] When the crosslinking agent is a polyhydroxy compound, the crosslinkable composition of the present invention preferably contains a crosslinking accelerator. The crosslinking accelerator can accelerate the formation of intramolecular double bonds in the dehydrofluorination reaction of the polymer main chain and the addition of the polyhydroxy compound to the formed double bonds.
[0093] As the crosslinking accelerator, an onium compound can be mentioned. Among the onium compounds, preferably at least one selected from the group consisting of ammonium compounds such as quaternary ammonium salts, phosphonium compounds such as quaternary phosphonium salts, oxonium compounds, sulfonium compounds, cyclic amines and monofunctional amine compounds is selected, and more preferably at least one selected from the group consisting of quaternary ammonium salts and quaternary phosphonium salts.
[0094] The quaternary ammonium salt is not particularly limited, and examples thereof include 8-methyl-1,8-diazabicyclo[5.4.0]-7-undecenium chloride, 8-methyl-1,8-diazabicyclo[5.4.0]-7-undecenium iodide, 8-methyl-1,8-diazabicyclo[5.4.0]-7-undecenium hydroxide, 8-methyl-1,8-diazabicyclo[5.4.0]-7-undecenium methyl sulfate, 8-ethyl-1,8-diazabicyclo[5.4.0]-7-undecenium bromide, 8-propyl-1,8-diazabicyclo[5.4.0]-7-undecenium bromide, 8-dodecyl-1,8-diazabicyclo[5.4.0]-7-undecenium chloride, 8- Dodecyl-1,8-diazabicyclo[5,4,0]-7-undecenium hydroxide, 8-eicosyl-1,8-diazabicyclo[5.4.0]-7-undecenium chloride, 8-tetracosyl-1,8-diazabicyclo[5.4.0]-7-undecenium chloride, 8-benzyl-1,8-diazabicyclo[5.4.0]-7-undecenium chloride (hereinafter referred to as DBU-B), 8-benzyl-1,8-diazabicyclo[5.4.0]-7-undecenium hydroxide, 8-phenethyl-1,8-diazabicyclo[5.4.0]-7-undecenium chloride, 8-(3-phenylpropyl)-1,8-diazabicyclo[5.4.0]-7-undecenium chloride, and the like. Among these, DBU-B is preferred because of its excellent crosslinking properties and various physical properties.
[0095] The quaternary phosphonium salt is not particularly limited, and examples thereof include tetrabutylphosphonium chloride, benzyltriphenylphosphonium chloride (hereinafter referred to as BTPPC), benzyltrimethylphosphonium chloride, benzyltributylphosphonium chloride, tributylallylphosphonium chloride, tributyl-2-methoxypropylphosphonium chloride, benzylphenyl(dimethylamino)phosphonium chloride, and the like. Among these, benzyltriphenylphosphonium chloride (BTPPC) is preferred from the viewpoint of excellent crosslinking properties and various physical properties.
[0096] When the crosslinking agent is a polyhydroxy compound, the fluorine-containing elastomer vulcanization accelerator containing bisphenol AF as a crosslinking agent disclosed in Japanese Patent Laid-Open No. 11-147891 and the adduct of a quaternary phosphonium salt containing a polyhydroxy compound as a crosslinking agent and a polyhydroxy compound described in Japanese Patent Laid-Open No. 2010-150563 can also be used. When these compounds (mixtures) are used as the crosslinking agent and the crosslinking accelerator, the content (parts by mass) of the crosslinking agent is the value obtained by removing the content of the crosslinking accelerator in the compound from the content of the compound relative to 100 parts by mass of the fluororubber.
[0097] The content of the crosslinking accelerator is not particularly limited, but is preferably 0.05 to 5 parts by mass, more preferably 0.5 to 1 part by mass, based on 100 parts by mass of the fluororubber.
[0098] When the vulcanization accelerator for fluorinated elastomer disclosed in Japanese Unexamined Patent Publication No. 11-147891 or the adduct of a quaternary phosphonium salt and a polyhydroxy compound described in Japanese Unexamined Patent Publication No. 2010-150563 is used as the crosslinking agent and the crosslinking accelerator, the content of the crosslinking accelerator is a value obtained by subtracting the content of the crosslinking agent in the compound from the content of these compounds relative to 100 parts by mass of the fluororubber.
[0099] As the pyridinium salt, the pyridinium salt described in JP-T 2018-514627A can be mentioned. As a preferred content of the pyridinium salt, the content described in JP-T 2018-514627A can also be applied to the crosslinkable composition of the present invention.
[0100] When the crosslinking agent is a pyridinium salt, the crosslinkable composition of the present invention preferably contains a basic compound. As the basic compound, the basic compounds described in JP-T 2018-514627 can be cited. As a preferred content of the basic compound, the content described in JP-T 2018-514627 can also be applied to the crosslinkable composition of the present invention.
[0101] The organic peroxide is not particularly limited as long as it is a crosslinking agent generally used in peroxide crosslinking, and may be an organic peroxide that easily generates peroxide radicals in the presence of heat or a redox system. Specifically, 1,1-bis(tert-butylperoxy)-3,5,5-trimethylcyclohexane, 2,5-dimethylhexane-2,5-dihydroperoxide, di-tert-butyl peroxide, tert-butylcumyl peroxide, dicumyl peroxide, α,α'-bis(tert-butylperoxy)-p-diisopropylbenzene, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, benzoyl peroxide, tert-butylbenzene peroxide, 2,5-dimethyl-2,5-di(benzoylperoxy)hexane, tert-butylperoxymaleate, tert-butylperoxyisopropylcarbonate, tert-butylperoxybenzoate, and the like may be cited. Among these, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane and 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne are preferred.
[0102] The content of the organic peroxide is preferably 0.05 to 10 parts by mass, more preferably 1.0 to 5 parts by mass, based on 100 parts by mass of the fluororubber.
[0103] When the crosslinking agent is an organic peroxide, the crosslinkable composition of the present invention preferably contains a multifunctional crosslinking auxiliary agent. Examples of the multifunctional crosslinking auxiliary agent include triallyl cyanurate, trimethylallyl isocyanurate, triallyl isocyanurate (TAIC), 1,3,5-triacryloyl hexahydro-s-triazine, triallyl trimellitate, N,N'-m-phenylene bismaleimide, dipropargyl terephthalate, diallyl phthalate, tetraallyl terephthalamide, triallyl phosphate, bismaleimide, triallyl fluoride isocyanurate (1,3,5-tris(2,3,3-trifluoro-2-propenyl) -1,3,5-triazine-2,4,6-trione), tri(diallylamine)-s-triazine, triallyl phosphite, N,N-diallylacrylamide, 1,6-divinyldodecafluorohexane, hexaallylphosphoramide, N,N,N',N'-tetraallylphthalamide, N,N,N',N'-tetraallylmalonamide, trivinyl isocyanurate, 2,4,6-trivinylmethyltrisiloxane, tri(5-norbornene-2-methylene)cyanurate, triallyl phosphite, etc. Among these, triallyl isocyanurate (TAIC) is preferred. When mixing fluororubber with a multifunctional crosslinking aid, a substance obtained by impregnating a multifunctional crosslinking aid in an inactive inorganic powder or the like can be used.
[0104] The content of the polyfunctional crosslinking aid is preferably 0.1 to 10 parts by mass, more preferably 0.5 to 5 parts by mass, based on 100 parts by mass of the fluororubber.
[0105] (Other ingredients)
[0106] The crosslinkable composition of the present invention may or may not contain an acid acceptor within a range that does not impair the desired effect exerted by the crosslinkable composition of the present invention. Examples of the acid acceptor include metal oxides such as magnesium oxide, calcium oxide, hydrotalcite, bismuth oxide, and zinc oxide, metal hydroxides such as calcium hydroxide, alkali metal silicates such as sodium metasilicate described in JP-A-2011-522921, and metal salts of weak acids described in JP-A-2003-277563. Examples of metal salts of weak acids include carbonates, benzoates, oxalates, and phosphites of Ca, Sr, Ba, Na, and K.
[0107] The acid acceptor is preferably at least one selected from the group consisting of metal oxides, metal hydroxides, alkali metal silicates, hydrotalcites, and metal salts of weak acids.
[0108] In one embodiment of the crosslinkable composition of the present invention, at least one metal compound selected from the group consisting of alkali metals, alkali metal oxides, alkali metal hydroxides, alkali metal salts, alkaline earth metals, alkaline earth metal oxides, alkaline earth metal hydroxides and alkaline earth metal salts may be contained or not contained, and the content of the above metal compound is 0 to 1 part by mass relative to 100 parts by mass of fluororubber. When the crosslinkable composition of the present invention has such a structure, there is a tendency that the acid resistance of the obtained molded article is further improved. The content of the above metal compound is preferably 0.5 parts by mass or less, more preferably 0.1 parts by mass or less, and particularly preferably not contained.
[0109] In one embodiment of the crosslinkable composition of the present invention, an acid acceptor such as calcium hydroxide, magnesium oxide, or hydrotalcite may be contained, and the content of the acid acceptor is 0 to 1 part by mass relative to 100 parts by mass of the fluororubber. When the crosslinkable composition of the present invention has such a structure, the acid resistance of the obtained molded article tends to be further improved.
[0110] The crosslinkable composition of the present invention may be mixed with various additives such as conventional additives mixed with fluororubber crosslinkable compositions, such as fillers (carbon black, bituminous coal, barium sulfate, diatomaceous earth, calcined clay, talc, etc.), processing aids (wax, etc.), plasticizers, colorants, stabilizers, adhesives (coumarone resins, coumarone-indene resins, etc.), mold release agents, electrical conductivity-imparting agents, thermal conductivity-imparting agents, surface non-adhesives, flexibility-imparting agents, heat resistance-improving agents, flame retardants, foaming agents, and antioxidants described in International Publication No. 2012 / 023485, as needed. It may also be mixed with one or more conventional crosslinking agents and crosslinking accelerators different from the above.
[0111] As fillers, there can be mentioned metal oxides such as titanium oxide and aluminum oxide; metal hydroxides such as magnesium hydroxide and aluminum hydroxide; carbonates such as magnesium carbonate, aluminum carbonate, calcium carbonate, and barium carbonate; silicates such as magnesium silicate, calcium silicate, and aluminum silicate; sulfates such as aluminum sulfate, calcium sulfate, and barium sulfate; metal sulfides such as molybdenum disulfide, iron sulfide, and copper sulfide; diatomaceous earth, asbestos, zinc barium white (zinc sulfide / barium sulfide), graphite, carbon fluoride, calcium fluoride, coke, quartz powder, talc, mica powder, wollastonite, carbon fiber, aramid fiber, various whiskers, glass fiber, organic reinforcing agent, organic filler, polytetrafluoroethylene, fluorine-containing thermoplastic resin, mica, silica, diatomaceous earth, clay, etc.
[0112] The content of fillers such as carbon black is not particularly limited, but is preferably 0 to 300 parts by mass, more preferably 1 to 150 parts by mass, further preferably 2 to 100 parts by mass, and particularly preferably 2 to 75 parts by mass, based on 100 parts by mass of the fluororubber.
[0113] The content of processing aids such as wax is preferably 0 to 10 parts by mass, more preferably 0 to 5 parts by mass, relative to 100 parts by mass of fluororubber. If processing aids, plasticizers, and mold release agents are used, the mechanical properties and sealing properties of the resulting molded product tend to be reduced, so these contents need to be adjusted within the range allowed by the properties of the target molded product.
[0114] The crosslinkable composition of the present invention may contain a dialkyl sulfone compound. Examples of the dialkyl sulfone compound include dimethyl sulfone, diethyl sulfone, dibutyl sulfone, methyl ethyl sulfone, diphenyl sulfone, and cyclopentane. The content of the dialkyl sulfone compound is preferably 0 to 10 parts by mass, more preferably 0 to 5 parts by mass, and particularly preferably 0 to 3 parts by mass relative to 100 parts by mass of the fluororubber. When the crosslinkable composition of the present invention contains a dialkyl sulfone compound, the lower limit of the content of the dialkyl sulfone compound may be, for example, 0.1 parts by mass or more relative to 100 parts by mass of the fluororubber.
[0115] The crosslinkable composition of the present invention is obtained by kneading fluororubber, solid solution, crosslinking agent, multifunctional crosslinking aid, crosslinking accelerator, filler, etc. using a commonly used rubber kneading device. As the rubber kneading device, a roll, a kneader, a Banbury mixer, a closed mixer, a twin-screw extruder, etc. can be used.
[0116] (Moulded product)
[0117] By crosslinking the crosslinkable composition of the present invention, a molded article can be obtained.
[0118] As a method for crosslinking the crosslinkable composition of the present invention, it is needless to say that commonly used methods such as pressure crosslinking, steam crosslinking, and oven crosslinking can be used. The crosslinking reaction can be carried out under any conditions, such as normal pressure, pressure, reduced pressure, and in the air. As the crosslinking conditions, they can be appropriately determined according to the type of crosslinking agent used, and are usually heated at a temperature of 150°C to 300°C for 1 minute to 24 hours. In the case of pressure crosslinking and steam crosslinking, it is preferably carried out at a temperature of 150°C to 180°C, and the crosslinking time is preferably carried out until the crosslinking time T90, for example, 1 minute to 2 hours. In the case of subsequent oven crosslinking (after pressure crosslinking or steam crosslinking), it is preferably carried out at a temperature of 170°C to 250°C, but it is not necessarily required. The crosslinking time of the oven crosslinking is preferably 0 to 48 hours, for example.
[0119] The crosslinkable composition of the present invention can also be molded to obtain a molded article. Molding can be performed by a conventionally known method, and examples thereof include compression molding, injection molding, extrusion molding, and calendar molding.
[0120] Examples of the use form of the molded product include various sealing materials or gaskets such as rings, gaskets, washers, diaphragms, oil seals, bearing seals, lip seals, plunger seals, door seals, lip and end seals, gas transport plate seals, wafer support seals, and barrel seals. As a sealing material, it can be used for applications requiring heat resistance, solvent resistance, chemical resistance, and non-adhesiveness.
[0121] In addition, the molded products can also be used as pipes, hoses, rollers, various rubber rollers, flexible joints, rubber sheets, coatings, belts, shock absorbers, valves, valve seats, valve bodies, chemical-resistant coating materials, laminating materials, lining materials, etc.
[0122] The cross-sectional shapes of the above-mentioned rings, gaskets and seals can be various shapes, specifically, they can be square, O-shaped, ring-shaped, etc., or they can be D-shaped, L-shaped, T-shaped, V-shaped, X-shaped, Y-shaped and other special shapes.
[0123] The crosslinkable composition of the present invention can be suitably used to obtain a molded article in contact with one or both of ammonia and urea. Therefore, the present invention relates to a crosslinkable composition for forming a molded article in contact with one or both of ammonia and urea, and more specifically, to the use of a crosslinkable composition for obtaining a molded article in which volume change and mass change are suppressed when in contact with one or both of ammonia and urea.
[0124] The molded article obtained from the crosslinkable composition has excellent resistance to urea water and ammonia water, and also excellent heat resistance. Therefore, the present invention also relates to the use of the molded article obtained from the crosslinkable composition for suppressing the volume change and mass change of the molded article when it comes into contact with one or both of ammonia and urea.
[0125] In one embodiment of the molded article of the present invention, the molded article has a contact surface that contacts one or both of ammonia and urea, and at least the contact surface is composed of a molded article obtained by crosslinking the crosslinkable composition. That is, the molded article obtained from the crosslinkable composition can be used to form at least the contact surface that contacts one or both of ammonia and urea in the molded article that contacts one or both of ammonia and urea.
[0126] The molded articles that come into contact with one or both of ammonia and urea include molded articles (e.g., containers, hoses, seals, gaskets, etc.) that may come into contact with one or both of ammonia and urea in standard use. Examples of these molded articles include molded articles used in automobile exhaust systems and molded articles used in manufacturing systems using ammonia or urea (e.g., reaction vessels, pipes, sealing materials).
[0127] The molded article that comes into contact with one or both of ammonia and urea can be used for storage, supply, transportation, reaction, metering and management of ammonia or urea. Examples of the molded article that comes into contact with one or both of ammonia and urea include tanks, hoses and tank cover seals; supply components such as hoses and pipes; valves; diaphragms; injection components; reaction components (such as SCR); reaction containers (i.e., containers where reactions occur); shaft seals; and connection components such as O-rings.
[0128] The molded product is particularly suitable for use as a component constituting a urea SCR system.
[0129] The urea SCR system is an exhaust gas purification device that uses urea water to purify nitrogen oxides exhausted from a diesel engine. The components constituting the urea SCR system are used in the urea SCR system, and may be, for example, sealing materials, gasket materials, pipes or tanks.
[0130] Figure 11 shows an example of a urea SCR system using components constituting a urea SCR system. The urea SCR system 10 includes an exhaust pipe 12 for discharging exhaust gas discharged from an engine (not shown) to the outside. The engine exhaust pipe 12 is provided with an oxidation catalyst 11, an SCR catalyst 13, and an oxidation catalyst 14. Urea water 18 is stored in a tank 15, sprayed into the exhaust pipe 12 by a pump 16 and an injection device 17, and is converted into ammonia gas by hydrolysis at high temperature. The exhaust gas containing nitrogen oxides discharged from the engine reaches the SCR catalyst 13 together with the urea water (ammonia gas) after passing through the oxidation catalyst 11, and the nitrogen oxides in the exhaust gas are selectively reduced and purified. The purified exhaust gas is discharged to the outside after passing through the oxidation catalyst 14. A DPF (Diesel particulate filter: not shown) for capturing particulate matter (PM) in the exhaust gas may also be provided immediately after the oxidation catalyst 11.
[0131] The components constituting the urea SCR system can be suitably used as components that come into contact with one or both of ammonia and urea. Even when in contact with one or both of ammonia and urea, the volume and mass are not likely to change, and the tensile strength is not likely to decrease even when used in a high temperature environment.
[0132] Therefore, the components constituting the urea SCR system can be used as the urea water supply pipe 19 for supplying urea water 18 from the tank 15 to the exhaust pipe 12, as a sealing material (not shown) used when connecting the urea water supply pipe 19 to the tank 15, the pump 16 or the injection device 17, and as a sealing material or a gasket material for various sensors. It is also preferable to use the components constituting the urea SCR system as a sealant (not shown) of a joint, and connect a plurality of pipes to form the urea water supply pipe 19.
[0133] Although the embodiments have been described above, it should be understood that various modifications may be made to the embodiments and details without departing from the spirit and scope of the claims.
[0134] <1> According to a first aspect of the present invention, there is provided a cross-linkable composition comprising a fluororubber and a solid solution of aluminum oxide and magnesium oxide.
[0135] <2> According to a second aspect of the present invention, there is provided the cross-linkable composition according to the first aspect, wherein the fluororubber is at least one selected from the group consisting of vinylidene fluoride-based fluororubbers and tetrafluoroethylene / propylene-based fluororubbers.
[0136] <3> According to a third aspect of the present invention, there is provided the cross-linkable composition according to the first aspect or the second aspect, wherein the content of the solid solution is 0.5 to 10 parts by mass based on 100 parts by mass of the fluororubber.
[0137] <4> According to a fourth aspect of the present invention, there is provided a cross-linkable composition according to any one of the first to third aspects, further comprising a cross-linking agent.
[0138] <5> According to a fifth aspect of the present invention, there is provided the cross-linkable composition according to the fourth aspect, wherein the cross-linking agent is an organic peroxide.
[0139] <6> According to a sixth aspect of the present invention, there is provided a crosslinkable composition according to any one of the first to fifth aspects, further comprising a polyfunctional crosslinking aid.
[0140] <7> According to a seventh aspect of the present invention, there is provided a cross-linkable composition according to any one of the first to sixth aspects, which contains or does not contain at least one metal compound selected from the group consisting of alkali metals, alkali metal oxides, alkali metal hydroxides, alkali metal salts, alkaline earth metals, alkaline earth metal oxides, alkaline earth metal hydroxides and alkaline earth metal salts, wherein the content of the metal compound is 0 to 1 part by mass relative to 100 parts by mass of the fluororubber.
[0141] <8> According to an eighth aspect of the present invention, there is provided a crosslinkable composition according to any one of the first to seventh aspects, which is used for forming a molded article in contact with one or both of ammonia and urea.
[0142] <9> According to a ninth aspect of the present invention, there is provided a molded article obtained by crosslinking the crosslinkable composition according to any one of the first aspect to the eighth aspect.
[0143] <10> According to a tenth aspect of the present invention, there is provided the molded article according to the ninth aspect, which is in contact with one or both of ammonia and urea.
[0144] <11> According to an eleventh aspect of the present invention, there is provided a molded article having a contact surface with one or both of ammonia and urea, wherein at least the contact surface is composed of a molded article obtained by crosslinking the crosslinkable composition according to any one of the first to eighth aspects.
[0145] <12> According to a twelfth aspect of the present invention, there is provided a molded article according to any one of the ninth to eleventh aspects, which is a component constituting a urea SCR system.
[0146] Example
[0147] Next, embodiments of the present invention will be described with reference to examples, but the present invention is not limited to the examples.
[0148] Each numerical value in the examples was measured by the following method.
[0149] <Monomer composition of fluoroelastomer>
[0150] use 19 The measurement was performed by F-NMR (AC300P model manufactured by Bruker).
[0151] <Iodine Content>
[0152] Na2CO3 and K2CO3 are mixed in a ratio of 1 to 1 (weight ratio), and the obtained mixture is dissolved in 20 ml of pure water to prepare an absorption liquid. 5 mg Na2SO3 is mixed in 12 mg of a sample (fluororubber) and a mixture is prepared, and it is burned in oxygen in a quartz flask, and the generated combustion gas is introduced into the absorption liquid. After the obtained absorption liquid is placed for 30 minutes, the concentration of iodine ions in the absorption liquid is measured using Shimadzu 20A ion chromatography. The calibration curve made using a KI standard solution containing 0.5 ppm of iodine ions and a KI standard solution containing 1.0 ppm is used to determine the content of iodine ions.
[0153] <Mooney viscosity>
[0154] The measurement was performed in accordance with ASTM D1646-15 and JIS K6300-1: 2013. The measurement temperature was 121°C.
[0155] <Heat of Fusion>
[0156] Using a differential scanning calorimeter (DSC822e manufactured by Mettler Toredo or X-DSC7000 manufactured by Hitachi High-Tech Science), 10 mg of a sample was heated at 20°C / min to obtain a DSC curve, and the heat of fusion was calculated from the magnitude of the melting peak (ΔH) appearing in the DSC curve.
[0157] <Crosslinking properties (maximum torque (MH), optimal crosslinking time (T90))>
[0158] For the crosslinkable composition, a crosslinking curve was obtained using a vulcanization tester (MDR H2030, manufactured by M&K Co.) under the conditions shown in Table 1 during primary crosslinking, and the maximum torque (MH) and the optimal crosslinking time (T90) were obtained from the change in torque.
[0159] <Tenable strength and elongation at break>
[0160] A dumbbell No. 6 shaped test piece was prepared using a crosslinked sheet having a thickness of 2 mm. The tensile strength and elongation at break at 23° C. were measured using the obtained test piece and a tensile tester (Tensilon RTG-1310 manufactured by A&D Co.) at 500 mm / min in accordance with JIS K6251:2010.
[0161] <Hardness>
[0162] Three crosslinked sheets each having a thickness of 2 mm were stacked and used, and the hardness (peak value, value after 3 seconds) was measured using a type A durometer in accordance with JIS K6253-3:2012.
[0163] <Urea water resistance>
[0164] A cross-linked sheet with a thickness of 2 mm was immersed in urea water (manufactured by Shin Nippon Chemical Co., Ltd., AdBlue (registered trademark)) at 90°C for 168 hours, and the cross-linked sheet was recovered. The specific gravity and mass of the cross-linked sheet before and after immersion were measured, and the volume change rate and mass change rate were calculated according to the following formula. The specific gravity was measured using an automatic densimeter DMA-220H (manufactured by Shinko Kogyo Co., Ltd.).
[0165] Volume change rate (%) = {[(mass of the cross-linked sheet after immersion) / (specific gravity of the cross-linked sheet after immersion)] - [(mass of the cross-linked sheet before immersion) / (specific gravity of the cross-linked sheet before immersion)]} / [(mass of the cross-linked sheet before immersion)] / (specific gravity of the cross-linked sheet before immersion)] × 100
[0166] Mass change rate (%) = [(mass of the cross-linked sheet after immersion) - (mass of the cross-linked sheet before immersion)] / (mass of the cross-linked sheet before immersion) × 100
[0167] <Ammonia water resistance>
[0168] A cross-linked sheet with a thickness of 2 mm was immersed in 10 mass % ammonia water at 40° C. for 168 hours or 504 hours, and the cross-linked sheet was recovered. The specific gravity and mass of the cross-linked sheet before and after immersion were measured, and the volume change rate and mass change rate were calculated according to the following formula. The specific gravity was measured using an automatic densimeter DMA-220H (manufactured by Shinko Electronics Co., Ltd.).
[0169] Volume change rate (%) = {[(mass of the cross-linked sheet after immersion) / (specific gravity of the cross-linked sheet after immersion)] - [(mass of the cross-linked sheet before immersion) / (specific gravity of the cross-linked sheet before immersion)]} / [(mass of the cross-linked sheet before immersion)] / (specific gravity of the cross-linked sheet before immersion)] × 100
[0170] Mass change rate (%) = [(mass of the cross-linked sheet after immersion) - (mass of the cross-linked sheet before immersion)] / (mass of the cross-linked sheet before immersion) × 100
[0171] <Heat resistance>
[0172] A dumbbell No. 6 shaped test piece was prepared using a cross-linked sheet having a thickness of 2 mm. The obtained test piece was heat treated at 240°C for 72 hours, and the tensile strength of the heat treated test piece was measured by the above method. Then, for the tensile strength, the change rate of the measured value before and after the heat treatment was calculated according to the following formula.
[0173] ΔX=(X-X0) / X0×100
[0174] ΔX: Tensile strength change rate (%)
[0175] X0: The measured value before heat treatment
[0176] X: The measured value after heat treatment
[0177] In Examples and Comparative Examples, the following materials were used.
[0178] Fluoroelastomer A
[0179] Vinylidene fluoride / tetrafluoroethylene / hexafluoropropylene copolymer
[0180] Vinylidene fluoride / tetrafluoroethylene / hexafluoropropylene: 50 / 20 / 30 (molar ratio)
[0181] Iodine content: 0.25 mass %
[0182] Mooney viscosity (ML1+10(121℃)): 25
[0183] Heat of melting: Not confirmed in the second round
[0184] Carbon black: MT carbon (N2SA=8m 2 / g, DBP oil absorption = 43ml / 100g)
[0185] Peroxide: 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane
[0186] Multifunctional crosslinking additive: Triallyl isocyanurate
[0187] Additive-A: Solid solution of aluminum oxide and magnesium oxide (KW-2200 manufactured by Kyowa Chemical Industry Co., Ltd.) (MgO / Al2O3=59.5 / 34.5 (mass ratio))
[0188] Additive-B: Hydrotalcite (DHT-4A manufactured by Kyowa Chemical Industry Co., Ltd.)
[0189] Additive-C: magnesium oxide (Kyowamag 150 manufactured by Kyowa Chemical Industry Co., Ltd.)
[0190] Additive-D: Alumina (AKP-G07θ type crystal manufactured by Sumitomo Chemical Co., Ltd.)
[0191] Examples 1 to 2 and Comparative Examples 1 to 3
[0192] The components were mixed according to the formulation in Table 1 and kneaded on an open roll to prepare a crosslinkable composition. The maximum torque (MH) and the optimal crosslinking time (T90) of the obtained crosslinkable composition are shown in Table 1. Next, the crosslinkable composition was crosslinked by the primary crosslinking (pressure crosslinking) under the conditions described in Table 1 and the secondary crosslinking (oven crosslinking) under the conditions described in Table 1 to obtain a crosslinked sheet (thickness 2 mm). The evaluation results of the obtained crosslinked sheet are shown in Table 1.
[0193]
Claims
1. A cross-linkable composition comprising fluororubber and a solid solution of aluminum oxide and magnesium oxide.
2. The crosslinkable composition according to claim 1, wherein The fluororubber is at least one selected from the group consisting of vinylidene fluoride-based fluororubber and tetrafluoroethylene / propylene-based fluororubber.
3. The crosslinkable composition according to claim 1 or 2, wherein The content of the solid solution is 0.5 to 10 parts by mass based on 100 parts by mass of the fluororubber. 4 . The cross-linkable composition according to claim 1 , further comprising a cross-linking agent.
5. The crosslinkable composition according to claim 4, wherein The crosslinking agent is an organic peroxide. 6 . The crosslinkable composition according to claim 1 , further comprising a polyfunctional crosslinking aid.
7. The cross-linkable composition according to any one of claims 1 to 6, which contains or does not contain at least one metal compound selected from the group consisting of alkali metals, alkali metal oxides, alkali metal hydroxides, alkali metal salts, alkaline earth metals, alkaline earth metal oxides, alkaline earth metal hydroxides and alkaline earth metal salts, wherein the content of the metal compound is 0 to 1 part by mass based on 100 parts by mass of the fluororubber. 8 . The cross-linkable composition according to claim 1 , which is used to form a molded article to be in contact with one or both of ammonia and urea. 9 . A molded article obtained by crosslinking the crosslinkable composition according to claim 1 . 10 . The molded article according to claim 9 , which is in contact with one or both of ammonia and urea.
11. A molded article having a contact surface with one or both of ammonia and urea, wherein at least the contact surface is composed of a molded article obtained by crosslinking the crosslinkable composition according to any one of claims 1 to 8. 12 . The molded article according to claim 9 , which is a component constituting a urea SCR system.
Citation Information
Patent Citations
Manufacture of fluorine-containing elastic copolymer
JP1986057324B2
Apparatus for filtering and activating water or bath water
JP1992008118B2
Iodine cure sites having a bromo-production of perfluoropolymer
JP1992505341A
Production of a perfluoropolymer having iodine cure sites containing cyano
JP1992505345A
Emulsion polymerization of fluoroelastomer
JP1993013961B2